Changes in ventilation and its components in normal subjects during sleep. - Stradling, J R (1985)
Non-invasive measurements were made of ventilation, its derivatives, the contributions of abdomen and rib cage and arterial oxygen saturation in six healthy normal men whilst awake and during sleep. Minute ventilation fell significantly during slow wave (SW) sleep and rapid eye movement (REM) sleep (awake = 6.3 1 min-1, SW sleep = 5.7 1 min-1, REM sleep = 5.4 1 min-1; p less than 0.04). Mean inspiratory flow also fell significantly but timing was unchanged. The abdominal (diaphragmatic) contribution to ventilation fell very significantly during SW sleep but returned to awake levels during REM sleep (awake 54%, SW sleep 38%, REM sleep 56%; p less than 0.007). There were also significant falls in arterial oxygen saturation during SW and REM sleep (awake 97.3%, SW sleep 96.5%, REM sleep 96.2%; p less than 0.002). These falls represent reductions in arterial oxygen tension similar to those seen in patients with chronic airways obstruction and can be accounted for entirely by the associated reduction in ventilation.